Developing Electronic Health Record Algorithms That Accurately Identify Patients With Systemic Lupus Erythematosus. Issue 5 (10th April 2017) - Barnado, April; Casey, Carolyn; Carroll, Robert J.; Wheless, Lee; Denny, Joshua C.; Crofford, Leslie J.
Abstract : Objective: To study systemic lupus erythematosus (SLE) in the electronic health record (EHR), we must accurately identify patients with SLE. Our objective was to develop and validate novel EHR algorithms that use International Classification of Diseases, Ninth Revision (ICD‐9), Clinical Modification codes, laboratory testing, and medications to identify SLE patients. Methods: We used Vanderbilt's Synthetic Derivative, a de‐identified version of the EHR, with 2.5 million subjects. We selected all individuals with at least 1 SLE ICD‐9 code (710.0), yielding 5, 959 individuals. To create a training set, 200 subjects were randomly selected for chart review. A subject was defined as a case if diagnosed with SLE by a rheumatologist, nephrologist, or dermatologist. Positive predictive values (PPVs) and sensitivity were calculated for combinations of code counts of the SLE ICD‐9 code, a positive antinuclear antibody (ANA), ever use of medications, and a keyword of "lupus" in the problem list. The algorithms with the highest PPV were each internally validated using a random set of 100 individuals from the remaining 5, 759 subjects. Results: The algorithm with the highest PPV at 95% in the training set and 91% in the validation set was 3 or more counts of the SLE ICD‐9 code, ANA positive (≥1:40), and ever use of both disease‐modifying antirheumatic drugs and steroids, while excluding individuals with systemic sclerosis and dermatomyositis ICD‐9 codes. Conclusion: We developed and validated the first EHR algorithm that incorporates laboratory values and medications with the SLE ICD‐9 code to identify patients with SLE accurately.